Pelatihan Pembuatan Buku Ajar menggunakan Artificial Inteligent (AI) di SDI Sekolah Embriyo Inspirator - Muhendra, Rifki; Kumalasari, Ratih; Rosihan, Rifda Ilahy; Hamdani, Haris (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
This community service activity aims to enhance the ability of teachers at SDI Sekolah Embriyo Inspirator in developing teaching materials using Artificial Intelligence (AI) technology. The background of this program is based on the importance of teaching materials as strategic tools to improve the quality of education. However, many teachers face challenges in creating teaching materials due to limited skills and knowledge. By leveraging advancements in AI, such as ChatGPT, Gemini, Bing Image Creator, Quillbot, and Mendeley, this activity was designed to provide practical and innovative solutions. Through a situational analysis, it was identified that SDI Sekolah Embriyo Inspirator, located in Tambun Selatan, has significant potential for educational development but requires capacity building for teachers to utilize technology effectively. The program was carried out in several stages, including preparation and socialization, training on AI-based teaching material development, hands-on practice in creating teaching materials, and evaluation and reporting. The activity, conducted on May 17, 2024, demonstrated high enthusiasm among teachers, who successfully applied various AI tools in their teaching material development practices. Additional discussions enriched participants’ knowledge of learning strategies. As a follow-up, continued collaboration is proposed for advanced training and the development of digital learning media. This program successfully provided a tangible impact in enhancing teachers' competencies and supporting the achievement of better educational quality in the digital era.